2018
DOI: 10.1097/psy.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Placebo Effects in Somatic Symptoms Through Oxytocin

Abstract: ObjectivePlacebo effects relieve various somatic symptoms, but it is unclear how they can be enhanced to maximize positive treatment outcomes. Oxytocin administration may potentially enhance placebo effects, but few studies have been performed, and they have had conflicting findings. The study aim was to investigate the influence of positive verbal suggestions and oxytocin on treatment expectations and placebo effects for pain and itch.MethodsOne hundred eight female participants were allocated to one of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 49 publications
(85 reference statements)
4
32
1
Order By: Relevance
“…In line with research into placebo effects on pain, experimental research has shown that the mere suggestion that an inert ointment is an active antipruritic drug can cause it to relieve itch . This effect does not appear robust however, as similar suggestions have not been observed to affect itch in other studies . Nocebo suggestions appear to have a more consistent effect on itch.…”
Section: Expectancy and Itchmentioning
confidence: 87%
“…In line with research into placebo effects on pain, experimental research has shown that the mere suggestion that an inert ointment is an active antipruritic drug can cause it to relieve itch . This effect does not appear robust however, as similar suggestions have not been observed to affect itch in other studies . Nocebo suggestions appear to have a more consistent effect on itch.…”
Section: Expectancy and Itchmentioning
confidence: 87%
“…Eighty healthy male volunteers between 18 and 36 years old participated in this study. Male participants were recruited since previous studies reported on the oxytocin boosting placebo analgesia in men 27 and not in women 38 and oxytocin fluctuations during the menstrual cycle can be an interfering factor in studying oxytocin effects in women. 33 Exclusion criteria were heart and lung diseases, high or low blood pressure, chronic or acute pain complains, heavy use of alcohol or other drugs, current diagnosis of psychiatric disorders, and current use of analgesic medications.…”
Section: Methodsmentioning
confidence: 99%
“…Kessner et al 27 demonstrated boosting effects of oxytocin on verbally induced placebo analgesia for experimentally induced pain. In contrast, Colloca et al 13 and Skvortsova et al 38 found no effects of oxytocin on verbally induced placebo analgesia. These 3 previous studies used verbal suggestions alone to induce placebo effects.…”
mentioning
confidence: 90%
“…Some studies have reported that intranasal oxytocin can enhance placebo analgesia [4] and even generate both placebo and nocebo effects in working memory performance [5] in men. However, several other recent studies on men [6] and women [7,8] found no evidence for effects of oxytocin. In an attempt to resolve these conflicting results Liu et al [9] have systematically re-evaluated the effects of intranasal oxytocin on placebo analgesia across sexes, dosages, and placebo effect induction paradigms in a large sample of subjects.…”
mentioning
confidence: 96%